The impact of sleep deprivation on cognitive function in healthy adults: insights from auditory P300 and reaction time analysis - Ren, Zhongkai; Mao, Xiang; Zhang, Ziyue; Wang, Wei (Frontiers in Neuroscience, 2025)
ObjectiveThis study aims to explore the effects of sleep deprivation on cognitive function in healthy adults, using auditory P300 event-related potentials and subjective reaction time as key assessment metrics.MethodsHigh-density electroencephalography (EEG) and the oddball paradigm were utilized to collect P300 event-related potentials (ERPs) before and after the sleep deprivation intervention, with a record of subjective reaction time. Participants were classified into acute sleep deprivation group and chronic sleep deprivation group based on the duration of their night shift history.ResultsFollowing sleep deprivation, a significant prolongation in P300 latency and reaction time was observed among 26 subjects (P < 0.05). Specifically, the reaction time in the acute group increased significantly by 83.69 ms after sleep deprivation (P < 0.05). In contrast, the reaction time in the chronic group exhibited only a minor increase of 6.54 ms (P < 0.05). Furthermore, a significant interaction effect between the duration of night shift history and sleep condition on reaction time was identified [F(aXb) = 4.736, P = 0.040, ηp2 = 0.165], suggesting that the influence of sleep deprivation on reaction time varies between the chronic and acute groups.ConclusionSleep deprivation induces cognitive impairment, with the acute sleep deprivation group experiencing more severe deficits. In contrast, the chronic sleep deprivation group demonstrated milder but chronic cognitive impairment.